Prevention and treatment of experimental thrombosis in rabbits with rivaroxaban (BAY 597939) – an oral, direct factor Xa inhibitor - Biemond, Bart J.; Perzborn, Elisabeth; Friederich, Philip W.; Levi, Marcel; Buetehorn, Ulf; Büller, Harry R. (Thrombosis and Haemostasis, 2007)
Current anticoagulant therapies for the prevention and treatment of thromboembolic disorders have many drawbacks: vitamin K antagonists interact with food and drugs and require frequent laboratory monitoring, and heparins require parenteral administration. Oral rivaroxaban (BAY 597939) is a new, highly selective and potent direct factor-Xa (FXa) inhibitor with a predictable pharmacodynamic and pharmacokinetic profile and could therefore be an attractive antithrombotic drug. It was the objective of this study to investigate the antithrombotic efficacy of oral rivaroxaban in two rabbit models of experimental venous thrombosis. In the venous stasis (prevention) model, animals were randomized to receive oral rivaroxaban 0.3, 1.0, 3.0 or 10.0 mg/kg or vehicle control. Thrombosis was induced by jugular vein stasis and injection of thromboplastin into the ear vein. In the venous thrombosis (treatment) model, intravenous (1.0 and 3.0 mg/kg) and oral (3.0 mg/kg) rivaroxaban was compared with intravenous nadroparin (40 U bolus and 20 U/h), fon-daparinux (42 Mg/kg) and vehicle control. Thrombus growth was assessed by measuring the accretion of radiolabeled fibrinogen into preformed clots in the jugular veins. Bleeding was assessed using an ear bleeding model. In the prevention model, rivaroxaban reduced thrombus formation dose-dependently (calculated ED50 1.3 mg/kg). In the treatment model, oral rivaroxaban (3.0 mg/kg) reduced thrombus growth to a similar extent to intravenous rivaroxaban (1.0 mg/kg), nadroparin and fondapari-nux. Oral rivaroxaban did not prolong bleeding time. In conclusion, the orally available selective, direct FXa inhibitor rivaroxaban is effective in the prevention and treatment of venous thrombosis in two well-established models of experimental thrombosis.
Keywords: Factor Xa inhibitor; venous thrombosis; prophylaxis; rivar-oxaban; oral anticoagulant